Soils for fine wines - White, R. E. (Robert Edwin), 1937- (Oxford University Press, 2003)
Annotation In recent years, viticulture has seen phenomenal growth, particularly in such countries as Australia, New Zealand, the United States, Chile, and South Africa. The surge in production of quality wines in these countries has been built largely on the practice of good enology and investment inhigh technology in the winery, enabling vintners to produce consistently good, even fine wines. Yet less attention has been paid to the influence of vineyard conditions on wines and their distinctiveness-an influence that is embodied in the French concept of terroir. An essential component ofterroir is soil and the interaction between it, local climate, vineyard practices, and grape variety on the quality of grapes and distinctiveness of their flavor. This book considers that component, providing basic information on soil properties and behavior in the context of site selection for newvineyards and on the demands placed on soils for grape growth and production of wines. Soils for Fine Wines will be of interest to professors and upper-level students in enology, viticulture, soils and agronomy as well as wine enthusiasts and professionals in the wine industry.